Blood Loss With Inhaled Anesthetic During First-Trimester Spontaneous Abortion Evacuation. Issue 3 (March 2022) - Montemorano, Lauren; Smith, Rachel M.; Payne, Nicolette; Cook, Meghan; Hayes, Blair H.; Hade, Erinn M.; Rivlin, Katherine; Isley, Michelle M.
Abstract : Inhaled anesthetic is associated with higher estimated blood loss and more frequent uterotonic use during first-trimester spontaneous abortion evacuation.